PREVENTION AND CONTROL MECHANISMS OF ANTIMICROBIAL RESISTANCE IN PRIMARY HEALTHCARE. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This annotation examines the importance of prevention and control mechanisms for antimicrobial resistance (AMR) within primary healthcare settings, where most initial patient encounters and antibiotic prescriptions take place. Antimicrobial resistance has become a global public health threat, driven largely by inappropriate antibiotic use, self-medication, incomplete treatment courses, and limited diagnostic capacity. Primary healthcare facilities play a critical role in early detection, rational prescribing, patient education, and community-level prevention strategies that can significantly reduce the burden of AMR.